Is adaptive gamification just a theoretical fairytale? An experiment in a text-based adventure game for data crowdsourcing - Weber, Mareike; Riar, Marc; Morschheuser, Benedikt (Proceedings of the 56th Hawaii International Conference on System Sciences (HICSS), 2023)
Gamification approaches are not always effective and vary in their success. Several studies suggest that unexpected results of effectiveness are related to a dearth of personalization of gamified systems following a one-size-fits-all (OSFA) approach. Although research indicates that gamification design that is dynamically adjusted to the preferences of the person using the system (i.e., adaptive gamification) can positively impact behavioral or motivational outcomes, there is still a gap in understanding the effectiveness of adaptive gamification. This work aims to advance our understanding on the impact of adaptive gamification on motivational and behavioral outcomes in the context of gamified crowdsourcing. To this end, an experiment (n=135) is conducted with a text-based adventure game that employs different versions of a narrative designed to address the specific needs of previously conceptualized distinct types of users (i.e., Hexad user types). The results show that adaptive gamification does not lead to higher behavioral outcomes, i.e., increased crowdsourcing participation, or motivational outcomes. Conclusively, this work challenges the common assumption of adaptive gamification based on player types being worth the effort. Moreover, the results show that general need satisfaction is associated with increasing motivational outcomes, independent of a user’s player type. Therefore, this work suggests focusing on different perceptions of need satisfaction being required by individuals rather than focusing on player types which are abstractions of reality.<br
Keywords: Diversity